The Influence of Work Environment, Motivation and Discipline Work On Teacher Job Satisfaction - Tampubulon, Vivian Natalie; Ariani, Misna; Arrywibowo, Imam (Universitas Syiah Kuala, 2025)
The aim of this study is to determine the influence of the environment Work , Motivation and Work Discipline on Teacher Job Satisfaction SMK Negeri 3 Balikpapan. In this study there was a population of 86 teachers and a sample of 60 respondents . The method used in this study was a statistical test with primary data from the distributed questionnaire . Data analysis using SmarPLS. The results of the study showed that partially the work environment and motivation had a positive effect on teacher job satisfaction. While work discipline did not succeed in influencing teacher job satisfaction.